An evolutionary Lagrange method for batch process optimal design. (1st January 2011) - Lin, Yung-Chin; Lin, Yung-Chien; Chang, Wen-Cheng; Su, Kuo-Lan
The optimal design of the multiproduct batch processes is one of the most important decision-making problems in the manufacturing industry. This decision-making problem can be formulated as a mixed-integer non-linear programming (MINLP) problem. In this paper, we propose an evolutionary Lagrange method to deal with such an MINLP problem. The computational results demonstrate the effectiveness of the algorithm in solving the optimal design problem of the multiproduct batch processes.